Profil Anggota Kelompok Perkumpulan Petani Pemakai Air (P3A) sebagai Unit Produksi dalam Menunjang Keberhasilan Usahatani Padi Sawah Lahan Pasang Surut di Kabupaten Indragiri Hilir - Legiman, Legiman; Tabrani, Gunawan; Syafrinal, Syafrinal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to describe the profile of P3A group members that influence production unit in supporting the success of rice farming of tidal land in Indragiri Hilir District. Research has been conducted in Indragiri Hilir District in Kempas, Reteh and Keritang District started from September 2016 until February 2017, using survey method with descriptive analysis of regression and correlation. The results of this study indicate that members of P3A tidal land rice paddy in Indragiri Hilir, the majority members of P3A are senior high school educated, male, productive age, have small family members, had narrow land area, the majority work on private land and 68,67% of P3A farmers rice productivity in Indragiri Hilir District rice increase and highly increase. The any change in attitude of P3A paddy farmers in Indragiri Hilir District has an effect on rice productivity increase of 0,313 ton.ha-1 and has a pretty positive relationship to the variable self efficacy, motivation, interaction member, cohesion member and norms members in supporting the success of paddy rice farming tidal land. Self efficacy factors, work motivation, member among interaction, member cohesion, member norms and norms of P3A members in Indragiri Hilir Regency have a relationship with each other with strong correlation value. Keywords: Member profile, P3A, paddy rice farming, productivity